Targeted metabolomics reveals differences in the extended postprandial plasma metabolome of healthy subjects after intake of whole‐grain rye porridges versus refined wheat bread. Issue 7 (27th February 2017) - Shi, Lin; Brunius, Carl; Lindelöf, Magnus; Shameh, Souad Abou; Wu, Huaxing; Lee, Isabella; Landberg, Rikard; Moazzami, Ali A.
Abstract : Twenty‐one healthy subjects consumed six test breakfasts in a randomized cross‐over study. We used targeted NMR‐profiling and GC‐MS to investigated postprandial difference in 38 plasma metabolites. Essential amino acids in plasma before lunch reflected protein composition. Wheat bread leads to higher plasma concentrations of ketone bodies than rye porridges, shortly before lunch. The increase in acetate and butyrate after lunch was due to colonic fermentation of dietary fiber. However, difference was unrelated to inulin, GLP‐1, appetite and second meal glucose responses. Abstract : Scope: We previously found that whole‐grain (WG) rye porridges suppressed appetite and improved glucose metabolism. This study aimed to investigate potential plasma metabolites that may be related to differences in those appetite and glucose responses. Methods and results: Twenty‐one health subjects consumed six isocaloric breakfasts in a randomized cross‐over study. Plain WG rye porridges (40 and 55 g), rye porridge enriched with different inulin: gluten proportions (9:3 g; 6:6 g; 3:9 g), and a 55 g refined wheat bread (control) were served as part of complete breakfast, followed by a standardized lunch. NMR metabolomics assessed 36 plasma metabolites and short chain fatty acids were measured by GC‐MS from baseline up to 8 h. Pre‐lunch plasma essential amino acids reflected protein composition and post‐lunch plasma short chain fatty acids varied with fiber content in breakfasts. No correlations were observed between measured metabolites and glucose, insulin, or appetite responses. Conclusions: Differences in protein and fiber contents in breakfasts altered postprandial plasma amino acids and short chain fatty acids, respectively, but were unrelated to appetite and glucose responses. Further studies are warrant to identify the underlying mechanisms for the beneficial effects on appetite and second meal glucose responses after rye‐based foods.